PENGARUH PERAN KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KEPUASAN KERJA DI HOTEL BINTANG 4 DAN 5 DI JAWA BARAT - Zulkifli Harahap (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
The main factor of low employee performance is the level of employee job satisfaction in work is still low. Based on preliminary research, low job satisfaction is due to the lack of optimal leadership and low communications of 4 and 5 star hotel employees in West Java. This study aims to examine the influence of leadership and communication role on employee job satisfaction in 4 and 5 star Hotel in West Java. Research uses path analysis method (Path Analysis). In this study, the sample is the level of manager employees of 4 and 5 star hotels in West Java as many as 199 people. The result of this research concludes that there is direct influence of Leadership to Job Satisfaction equal to 17,18 percent, direct influence of Communication to Job Satisfaction is 4,96 percent. Simultaneously the effect of free variable to Job Satisfaction is 27.2 percent the rest of 72.8 percent is another factor that is not observed but also affects Job Satisfaction